How the Dead Sea Scrolls Were Found - Frank, Harry Thomas (The Biblical archaeology review, 1975)
The most sensational archaeological discovery of the last half century was made entirely by accident. On a morning in the winter of 1946-1947 three shepherds of the Ta’amireh tribe of Bedouin watched their nimble-footed goats skip across the cliffs just north of an old ruin on the northwest shore of the Dead Sea The […]